1999
DOI: 10.1111/j.1749-6632.1999.tb07978.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia‐Induced Ischemic Tolerance

Abstract: Delayed resistance to ischemic injury can be induced by a variety of conditioning stimuli. This phenomenon, known as delayed ischemic tolerance, is initiated over several hours or a day, and can persist for up to a week or more. The present paper describes recent experiments in which transient hypothermia was used as a conditioning stimulus to induce ischemic tolerance. A brief period of hypothermia administered 6 to 48 hours prior to focal ischemia reduces subsequent cerebral infarction. Hypothermia-induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 112 publications
0
22
0
Order By: Relevance
“…Nishio et al [4,27] demonstrated a significant reduction in infarct size by forced hypothermic preconditioning initiated 24 h before MCAO. Therefore, we also started induction of regulated hypothermic preconditioning at 26 h before MCAO and we obtained similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Nishio et al [4,27] demonstrated a significant reduction in infarct size by forced hypothermic preconditioning initiated 24 h before MCAO. Therefore, we also started induction of regulated hypothermic preconditioning at 26 h before MCAO and we obtained similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia-induced ischemic tolerance is initiated within 6 hours, peaks at approximately 1 or 2 days, and is reversed by 7 days after preconditioning stimulation. 13 It is likely that a hypothermic threshold must be reached for successful preconditioning to occur. Our findings support this possibility because T 0 AM failed to induce the same depth and duration of hypothermia as T 1 AM and failed to confer antecedent protection to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…26 In support of this postulate, hypothermia-induced preconditioning depends on de novo protein synthesis, and in SHSY5 cells, it requires modification of proteins by SUMOylation. 13,27 Transcription factors are the main targets of SUMO conjugation and SUMOylation of these proteins generally causes transcriptional suppression. Whether administration of T 1 AM and T 0 AM causes widespread SUMOylation of transcription factors is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular attention requires maintenance of normothermic conditions of the mice throughout the complete period of anesthesia because hypothermia itself has a preconditioning effect and can therefore interfere with the BCCAO effect 16 . In awake and freely moving rodents, core temperatures are approximately between 0.5 and 1 degree Celsius higher than the corresponding brain temperatures 17 .…”
Section: Representative Resultsmentioning
confidence: 99%